Crack Propagation Analysis in Metallic Alloys: A Comparative Study of Traditional and Advanced Materials - Nishant Varshney (International Journal of Fracture Mechanics and Damage Science, 2024)
A vital component of materials science and engineering, crack propagation analysis is essential to determining the structural integrity and dependability of materials. Designing safe and long-lasting structures for a variety of sectors required an understanding of how cracks begin, spread, and interact with a material's microstructure. To guarantee the performance, safety, and dependability of materials in a variety of applications, crack propagation analysis is essential. It offers insightful information about the fracture behavior of materials, that assists with material design, optimization, and the creation of stronger, longer-lasting structures and materials
Keywords: crack propagation; fatigue crack growth; fracture toughness; metallic alloys; stress intensity factor